Intimate partner violence experienced by women living with—and without—disability in the European Union. A quantitative intersectional analysis - Rodriguez Martinez, Pilar (Frontiers in Sociology, 2022)
This article aims to explore the specific combination and interactions of inequalities associated with experiencing Intimate Partner Violence that affects European women living with—or without—a disability. The analysis is based on the survey carried out by the European Union Agency for Fundamental Rights (FRA) between 2010 and 2012. In that survey, 42,002 women were interviewed, with a representative sample of women from each of the 28 countries of the European Union. We try to elucidate through a multiple logistic regression analysis if the experience of IPV is something that can simply be added to—or overlap with—social categories (feeling of household income, educational level, and marital status), the aggressor (partner abusing alcohol, partner violent against others), the relationship (duration, equal say in economic decisions), and the previous experience of IPV. The result of the analysis shows that living with a disability intersects with low income, which comes hand in hand with experiencing more violence. Other interactions like living with a disability when the woman is under 15 years and living with a disability and the partner abusing alcohol are also relevant. In terms of social policies, our result should induce investment in IPV prevention policies among poor women who live with a disability, who have a history of physical violence, and whose partners abuse alcohol.